2017
DOI: 10.1093/annonc/mdw556
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 study of twice weekly pulse dose and daily low-dose erlotinib as initial treatment for patients with EGFR-mutant lung cancers

Abstract: Background: Patients with EGFR-mutant lung cancers treated with EGFR tyrosine kinase inhibitors (TKIs) develop clinical resistance, most commonly with acquisition of EGFR T790M. Evolutionary modeling suggests that a schedule of twice weekly pulse and daily low-dose erlotinib may delay emergence of EGFR T790M. Pulse dose erlotinib has superior central nervous system (CNS) penetration and may result in superior CNS disease control. Methods:We evaluated toxicity, pharmacokinetics, and efficacy of twice weekly pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 41 publications
0
39
0
Order By: Relevance
“…Theoretical simulations of the Darwinian dynamics of drug-sensitive and -resistant subclones in heterogeneous cancers have described how evolutionary trade-offs (24,25), aggregation effects (26), variable cell densities (26)(27)(28), or spatial interactions (29) can create differential selective pressures among subclones and influence tumor evolution in response to therapy. These insights from mathematical oncology have inspired the design of "evolutionarily-enlightened therapies" (26), which consider factors such as future states of resistance (6,30), evolutionary trade-offs (31), and temporal subclone vulnerabilities (32), and predict optimal scheduling to guide clinical studies (33)(34)(35). Such models have also been used to study combination therapies for cancer (5)(6)(7)(8)(9), but more theoretical evolution work is needed to understand the long-term impact of synergistic (vs. nonsynergistic) therapy.…”
Section: B the Effect Of Combination Therapymentioning
confidence: 99%
“…Theoretical simulations of the Darwinian dynamics of drug-sensitive and -resistant subclones in heterogeneous cancers have described how evolutionary trade-offs (24,25), aggregation effects (26), variable cell densities (26)(27)(28), or spatial interactions (29) can create differential selective pressures among subclones and influence tumor evolution in response to therapy. These insights from mathematical oncology have inspired the design of "evolutionarily-enlightened therapies" (26), which consider factors such as future states of resistance (6,30), evolutionary trade-offs (31), and temporal subclone vulnerabilities (32), and predict optimal scheduling to guide clinical studies (33)(34)(35). Such models have also been used to study combination therapies for cancer (5)(6)(7)(8)(9), but more theoretical evolution work is needed to understand the long-term impact of synergistic (vs. nonsynergistic) therapy.…”
Section: B the Effect Of Combination Therapymentioning
confidence: 99%
“…This trial was an expansion cohort of a prospective, openlabel, single-center, phase 1 dose-escalation study in patients with EGFR-mutant lung cancers. 11 The trial was conducted after approval of the institutional review board at Memorial Sloan Kettering. The primary endpoints of the study were the overall and CNS responses according to version 1.1 of the Response Evaluation Criteria in Solid Tumors (RECIST 1.1).…”
Section: Methodsmentioning
confidence: 99%
“…We defined the maximum tolerated dose of erlotinib as 1200 mg on days 1 and 2 and as 50 mg on days 3 to 7. 11 Although this regimen did not delay the time to acquired resistance or prevent the emergence of T790M, no patient developed progression in the CNS. To follow up on this unexpected observation, we treated an additional cohort of patients with untreated brain metastases or leptomeningeal disease with this regimen.…”
Section: Introductionmentioning
confidence: 95%
“…Evolution matters. A recent (2012) systematic literature analysis of cancer 31 relapse and therapeutic research showed that while evolutionary terms rarely appeared in papers studying therapeutic relapse 32 before 1980 (< 1%), the use of evolutionary terms has steadily increased more recently, due to the potential benefits of studying 33 therapeutic relapse from an evolutionary perspective 23 . 34 A new paradigm in the war on cancer replaces the "treatment-for-cure" strategy with "treatment-for-contain" -receiving 35 cues from agriculturists who have similarly abandoned the goal of complete eradication of pests in favor of more limited and 36 strategic application of insecticides for control 21,24 .…”
mentioning
confidence: 99%
“…These adaptive therapies capitalize on competition for space and resources between drug-sensitive 46 and slow growing drug-resistant populations 13,29,30 . These trials have shown initial promise in prostate cancer compared with 47 contemporaneous patient cohorts 28 , but it should be noted that evolutionary modeling-based dosing schedule did not improve 48 progression-free survival in anti-cancer TKI regimens for patients with EGFR-mutant lung cancers 31 . 49 Steering patient-specific evolution 50 This adaptive approach means that each patient's treatment is truly personalized based on the tumor's state and response rather 51 than a one-size-fits-all fixed treatment regime 32 .…”
mentioning
confidence: 99%